La recuperación de los espacios públicos para la integración sociofamiliar en la cabecera cantonal El Guabo, período 2020-2023 - Curipoma Cuzco, Adriana Nicole; Montoya Macas, Vanessa Madelaine (Machala, 2024)
This research deals with "The recovery of public spaces for socio-family integration in the cantonal capital of El Guabo, period 2020-2023". The Public spaces are a factor of interconnections that enable the well-being and development of the population, that is, places that allow people to share moments in the company of family and friends, they fulfill different functions since society is composed of values, norms and criteria, the same in which different groups are incorporated without discrimination by race, age or belief orientation. In this sense, it is essential that the decentralized autonomous governments of each canton intervene in one way or another in the maintenance of these areas, since their deterioration is a problem that affects the local population and visitors. For this reason, a general objective was proposed, which is: To determine the contribution of public spaces in the socio-family integration in the cantonal capital of El Guabo, and four specific ones: To identify the effects of the deterioration of public spaces on socio-family integration, To establish the citizen perception of the importance of public spaces in the cantonal capital, Identify the characteristics of the existing public spaces in the cantonal capital of El Guabo and determine the strategies implemented by the municipal GAD El Guabo for the recovery of public spaces. The sociological approach applied is the structural-functional one of Emilie Durkheim and Radcliffe Brown, which contributes to the survival or adaptation that is had in a place, therefore the state as a regulatory entity must intervene for the recovery of public spaces and with it also the socio-family integration avoiding conflicts in the territory. Urban sociology is also considered because it studies the transformations of the city and seeks to understand how people interact within social organizations. On the other hand, urban sociology is mentioned because it focuses on an in-depth analysis of life in cities, which studies aspects related to the social, cultural and economic dynamics that interact and give structure to the experience of people in the environments of the metropolis. That is why the city is consolidated not only in its structure, but also in the customs and traditions of the individuals who reside there; In other words, it is endowed with both a moral organization and a material that also includes public spaces as meeting areas. The research that was proposed is basic in that its purpose is to broaden the understanding of the reality of the recovery of public spaces in the cantonal capital of El Guabo and to indicate the situation of this problem through interviews, surveys and observations. It has a descriptive character because this method of information is applied to the description that details the phenomenon in its entirety. It is usually done before an experiment to know the "what" of the subject of analysis and thus be able to describe the object to be studied. The research has a mixed methodological approach, that is, the combination of quantitative and qualitative methods in order to obtain a more complete and in-depth understanding of the problem. Therefore, the objective is to obtain responses from the population to questions that will be asked through the application of instruments such as interviews and surveys. The cantonal capital of El Guabo has been in trouble due to the deterioration caused by the lack of maintenance, insecurity and the poor state of the infrastructure. As a consequence, the quality of life, social interaction, sense of belonging, community participation and neighborhood relations are evidence of problems given that the infrastructure of these places was visualized presenting deterioration, accumulation of garbage on the ground, benches with signs of wear and unauthorized graffiti, however, the municipal GAD of El Guabo has not implemented specific strategies for the recovery of public spaces. For this reason, a greater intervention by the municipal GAD is necessary, despite the work they are doing, the infrastructure of public spaces should be improved in depth so that they are not harmed. It is also important that social, cultural or sports activities are carried out to encourage citizens to actively use public spaces, and in this way improve socio-family integration and strengthen the control and penalization of offenders who cause the destruction or restrict the use of public spaces.
La presente investigación analiza “La recuperación de los espacios públicos para la integración sociofamiliar en la cabecera cantonal El Guabo, período 2020-2023”. Los espacios públicos son un factor de interconexiones que posibilitan el bienestar y desarrollo de la población; es decir, son lugares que permiten a las personas compartir momentos en compañía de familiares y amistades, cumpliendo diferentes funciones dado a que la sociedad está compuesta de valores, normas y criterios, los mismo en los que se incorporan distintos grupos sin discriminación de raza, orientación edad o creencias. En tal sentido, se constituye un eje fundamental que los Gobiernos Autónomos Descentralizados intervengan de alguna u otra manera en el mantenimiento de estas áreas, ya que el deterioro de los mismos, es un problema que afecta a la población local y visitantes del sector. Por ello se planteó el objetivo general: Determinar la contribución de los espacios públicos en la integración socio familiar en la cabecera cantonal El Guabo, y el enfoque sociológico aplicado es el estructural-funcional de Emilie Durkheim y Radcliffe Brown lo que contribuye a favor de la supervivencia o adaptación que se tiene en un lugar, por ello el Estado como ente regulador debe intervenir para la recuperación de los espacios públicos y con ello también la integración sociofamiliar, evitando conflictos en el territorio, también se considera a la sociología urbana dado a que estudia las transformaciones de la ciudad y busca entender la interacción de las personas en las organizaciones sociales. Asimismo, la sociología urbana se enfoca a un análisis profundo de la vida en las ciudades, que estudia aspectos relacionados con las dinámicas sociales, culturales y económicas que interactúan y dan estructura a la experiencia de las personas en los entornos públicos. Es por ello que la ciudad está consolidada no solo en su estructura, sino también en las costumbres y tradiciones de los individuos que la residen; en otras palabras, está dotada tanto de una organización moral como de un material que además comprende a estos espacios como áreas de encuentro. La investigación propuesta es básica por cuanto tuvo como propósito ampliar la comprensión de la realidad sobre la recuperación de espacios públicos en la cabecera cantonal de El Guabo y se indica en qué situación se encuentra esta problemática a través de las entrevistas, encuestas y observaciones. Tiene un carácter descriptivo debido a que este método de información es aplicado dado la descripción que detalla al fenómeno en su totalidad, normalmente se realiza antes de un experimento para conocer el “que” del sujeto de análisis y así poder describir al objeto a estudiar. La investigación tiene un enfoque metodológico mixto, es decir, la combinación de métodos cuantitativos y cualitativos con la finalidad de obtener una comprensión más completa y profunda de la problemática. Por lo cual se tiene como propósito obtener respuestas de la población a preguntas que se efectuarán a partir de la aplicación de instrumentos como entrevistas y encuestas. La cabecera cantonal de El Guabo enfrenta desafíos significativos debido al deterioro provocado por la falta de mantenimiento, la inseguridad y el estado precario de su infraestructura. Estos problemas tienen repercusiones directas en diversos aspectos, tales como la calidad de vida, la interacción social, el sentido de pertenencia, la participación comunitaria y las relaciones vecinales. Además, se observa una acumulación de basura en el suelo, bancas con evidentes signos de desgaste y grafitis no autorizados. Sin embargo, el Gobierno Autónomo Descentralizado (GAD) municipal de El Guabo no ha implementado estrategias específicas para la recuperación de estos espacios públicos. Por tanto, se hace necesario mejorar la participación del GAD municipal. A pesar de los esfuerzos actuales, es crucial realizar mejoras sustanciales en la infraestructura de los espacios públicos para garantizar su preservación. Además, resulta fundamental la implementación de actividades sociales, culturales o deportivas que fomenten la participación activa de la ciudadanía en estos espacios, promoviendo así una mayor integración sociofamiliar. Asimismo, es esencial fortalecer la vigilancia y aplicación de sanciones a aquellos infractores que contribuyen a la degradación o limitan el uso adecuado de los espacios públicos.
Keywords: ESPACIO PUBLICO; INTEGRACION SOCIOFAMILIAR; RECUPERACION